Experimentation and rapid prototyping in support of counterterrorism (National Academies Press, 2009)
"The U.S. military forces currently face a nontraditional threat from insurgents and terrorists who primarily employ improvised explosive devices, and have shown a cycle of adaptation of less than 12 months to responses by U.S. forces to counter these attacks. This constantly evolving threat requires U.S. military forces to adapt and respond more rapidly with modified tactics, technologies, and/or equipment. In response to this need for new technologies, the Rapid Reaction Technology Office (RRTO) was established in 2006 to develop technologies that can mature in 6 to 18 months for purposes of counterterrorism. Although RRTO appears to be successfully fulfilling its mission, the agency seeks to understand and address barriers to and opportunities for meeting future counterterrorism needs--including the need to accelerate the transition of technologies for counterterrorism with an eye to countering emerging and anticipated threats. This book reviews RRTO approaches and provides a set of recommendations for potential improvements to help meet these needs for rapid technology development."--Publisher's description